Reaction mechanism conversion induced by the contest of nucleophile and leaving group. Issue 39 (28th September 2022) - Zhao, Siwei; Fu, Gang; Zhen, Wenqing; Yang, Li; Sun, Jianmin; Zhang, Jiaxu
Abstract : Reaction mechanism conversion caused by competition between leaving group and nucleophile in the X − + CH3 Y reactions. Abstract : Direct dynamic simulations have been employed to investigate the OH − + CH3 Cl reaction with the chosen B3LYP/aug-cc-pVDZ method. The calculated rate coefficient for the bimolecular nucleophilic substitution reaction (SN 2), 1.0 × 10 −9 cm 3 mol −1 s −1 at 300 K, agrees well with the experimental result of (1.3–1.6) × 10 −9 cm 3 mol −1 s −1 . The simulations reveal that the majority of the SN 2 reactions are temporarily trapped in the hydrogen-bonded complex at E coll = 0.89 kcal mol −1 . Importantly, the influences of the leaving group and nucleophile have been discussed by comparisons of X − + CH3 Y (X = F, OH; Y = Cl, I) reactions. For the X = F − reactions, the reaction probability of SN 2 increases along the increased leaving group ability Cl < I, suggesting that the thermodynamic factor plays a key role. The indirect mechanisms were found to be dominant for both reactions. In contrast, for X = OH −, the fraction of SN 2 drops with the enhanced leaving group ability. In particular, a dramatic transition occurs for the dominant atomic reaction mechanisms, i.e., from complex-mediated indirect to direct, implying an interesting contest between the leaving group and the nucleophile and the importance of the dynamic factors, i.e., the dipole moment, steric hindrance, and electronegativity.